Contraceptive behaviour of Christian and Muslim teenagers at the time of abortion and post-abortion in Thrace, Greece. (1st November 2016) - Tsikouras, Panagiotis; Koukouli, Zacharoula; Psarros, Nikolaos; Manav, Bachar; Tsagias, Nikolaos; Galazios, Georgios
Abstract: Objectives: The aims of the study were to compare the contraceptive behaviour of Christian and Muslim adolescents who had an abortion in Thrace, Greece, and to examine whether extensive contraceptive counselling at the time of abortion modified their subsequent contraceptive practices. Methods: Adolescents, aged 14–19 years, who had undergone an elective abortion in our department, were included in a prospective 12-year study. Extensive contraceptive counselling was offered before discharge from the hospital. Attitudes to contraception were assessed by means of a simple questionnaire at the time of abortion and at 1-year follow-up. Results: The study population comprised of 95 Christian Orthodox adolescents (Group A) and 79 Muslim adolescents (Group B). At the time of abortion, contraceptive behaviour differed significantly between the two groups ( p = .004). Contraceptive methods used in Group A in comparison with Group B were as follows: oral contraceptives (27.4% vs. 12.7%), condoms (22.1% vs. 38.0%), interrupted coitus (18.9% vs. 20.3%), periodic abstinence (16.8% vs. 25.3%) and emergency contraception (14.7% vs. 3.8%). The commonest source of information on contraception in Group A was the gynaecologist (17.9%) and family planning clinic (15.8%), whereas in Group B it was the individual's partner (25.3%) and parents (16.4%). Contraceptive behaviour was significantly modified in both groups at post-abortion follow-up (both p < .001). The original difference between the groups, however, persisted ( p = .006). In Group A, oral contraceptives were the dominant method (48.4%), followed by condoms (30.5%), whereas in Group B, the order was still the reverse (24.1% and 46.8%, respectively). Conclusion: Cultural differences significantly affect the contraceptive behaviour. Nevertheless, interventions that promote contraception can still be successful in different populations.